Trustworthy service discovery based on a modified ant colony algorithm - Guo-jun SHENG; Tao WEN; Quan GUO; Xiao-ying SONG (Tongxin xuebao)
Aiming at the problem of service discovery in unstructured P2P network,a trustworthy service discovery me-thod based on a modified ant colony algorithm was prop sed.Some novel policies were introduced to control the beha-vior of the ant colony,such as the dynamic ant colony policy,the sub-ant policy,the reputation evaluation policy to ser-vice peers,and the punishment policy to malicious peers.Service peers with high reputation could change their neighbors and make self-organization under the recommendation of ants.These policies and methods provide new ideas for the ap-plication researches of ant colony algorithms in the field of distributed service discovery.The results of experiments show that the proposed algorithm can guarantee higher trust service precision and better integrated service discovery performance in complex network environments,and some useful conclusions were obtained through the alysis and ex-planation of the experimental data,laying a solid foundation for further researches.